SOCIAL CONFLICT RESOLUTION RELATED TO BULLYING CASES THROUGH THE DELIBERATION SYSTEM BASED ON PANCASILA PERSPECTIVE - Handayani, Trini; Mulyana, Aji; Solihah, Cucu; Ramadani, Azzahra Salsabila; Putri, Kayla Andini; Setyowati, Endang (Semarang Law Review (SLR), 2024)
This article discusses the review of Social Conflict Resolution Related to Bullying Cases Through the Deliberation System Based on the Perspective of Pancasila. Bullying can be physical, verbal, and mental. Bullying cases in Indonesia are increasing and need serious handling. Deliberation based on Pancasila values can be a solution to resolve bullying conflicts peacefully and constructively. A culture of deliberation needs to be promoted in schools and communities to create a safe environment and respect for human rights. This article discusses the importance of resolving bullying-related social conflicts through a deliberation system based on the perspective of Pancasila. Bullying conflicts create tension and hostility in society, and if not properly addressed can affect the school and workplace environment. This research uses a normative juridical research method by referring to literature and internet materials. Bullying is a form of physical and psychological violence that can be experienced by anyone, and has long existed in society. Bullying is increasingly widespread in educational institutions, influenced by family, environmental, peer group, and media factors. Victims of bullying experience psychological, physical, social and academic impacts. Perpetrators of bullying also experience psychological, social, academic and long-term impacts. The resolution of bullying conflicts can be done through deliberation based on the values of Pancasila, but if not, the conflict can be resolved through deliberation.